Recent advances in dengue pathogenesis and clinical management. Issue 50 (10th December 2015) - Simmons, Cameron P.; McPherson, Kirsty; Van Vinh Chau, Nguyen; Hoai Tam, D.T.; Young, Paul; Mackenzie, Jason; Wills, Bridget
Abstract: This review describes and commentates on recent advances in the understanding of dengue pathogenesis and immunity, plus clinical research on vaccines and therapeutics. We expand specifically on the role of the dermis in dengue virus infection, the contribution of cellular and humoral immune responses to pathogenesis and immunity, NS1 and mechanisms of virus immune evasion. Additionally we review a series of therapeutic intervention trials for dengue, as well as recent clinical research aimed at improving clinical diagnosis, risk prediction and disease classification.